2002
DOI: 10.5194/angeo-20-1967-2002
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effects of the October 1989 solar proton event on mesospheric odd nitrogen using a detailed ion and neutral chemistry model

Abstract: Abstract. Solar proton events and electron precipitation affect the concentrations of middle atmospheric constituents. Ionization caused by precipitating particles enhances the production of important minor neutral constituents, such as nitric oxide, through reaction chains in which ionic reactions play an important role. The Sodankylä Ion Chemistry model (SIC) has been modified and extended into a detailed ion and neutral chemistry model of the mesosphere. Our steady-state model (containing 55 ion species, 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 41 publications
4
58
0
Order By: Relevance
“…The changing HANE-injected differential flux at L=1.57 during the operation of an assumed ground based RBR-system, in the same format as Fig. 4. time-scales, and altitudes of these changes are rather similar to the NO x /HO x enhancements and O 3 depletions calculated by the SIC model for large solar proton events (Verronen et al, 2002(Verronen et al, , 2005, confirmed by experimental observations using the GOMOS satellite-bourn instrument Verronen et al, 2005) and subionospheric VLF propagation measurements . Thus while RBR-forced precipitation should be expected to be a rare occurrence, even if it was used to mitigate the effects of intense natural injections while providing a defence against possible HANE-injections, the effects are no more significant than large solar proton events.…”
Section: Modelling Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The changing HANE-injected differential flux at L=1.57 during the operation of an assumed ground based RBR-system, in the same format as Fig. 4. time-scales, and altitudes of these changes are rather similar to the NO x /HO x enhancements and O 3 depletions calculated by the SIC model for large solar proton events (Verronen et al, 2002(Verronen et al, , 2005, confirmed by experimental observations using the GOMOS satellite-bourn instrument Verronen et al, 2005) and subionospheric VLF propagation measurements . Thus while RBR-forced precipitation should be expected to be a rare occurrence, even if it was used to mitigate the effects of intense natural injections while providing a defence against possible HANE-injections, the effects are no more significant than large solar proton events.…”
Section: Modelling Resultssupporting
confidence: 59%
“…Our study made use of SIC version 6.6.0. The model has recently been discussed by Verronen et al (2005), building on original work by Turunen et al (1996) and Verronen et al (2002). A detailed overview of the model was given in Verronen et al (2005), but we summarize in a similar way here to provide background for this study.…”
Section: Sodankylä Ion Chemistry Modelmentioning
confidence: 99%
“…This study makes use of SIC version 6.9.0. The model has recently been discussed by Verronen et al [2005], building on the original work by Turunen et al [1996] and Verronen et al [2002]. A detailed overview of the model was given by Verronen et al [2005].…”
Section: Nighttime Riometer Absorption Using the Sodankylä Ion And Nementioning
confidence: 99%
“…Initial descriptions of the model are provided by Turunen et al [1996], with neutral species modifications described by Verronen et al [2002]. Solar flux is calculated with the SOLAR2000 model (version 2.23) [Tobiska et al, 2000].…”
Section: Sodankylä Ion Chemistry (Sic) Modelmentioning
confidence: 99%
“…The Sodankylä ion chemistry model (SIC) [see Verronen et al, 2002] models the major chemical reactions and interactions known to occur in the lower ionosphere. It has been used to calculate the effects of a series of SPEs that took place in October/November 2003.…”
Section: Introductionmentioning
confidence: 99%